Clinical and epidemiological characteristics and microbiological profile of the infections associated with the health care of the hospital almanzor aguinaga asenjo, 2014 – 2016 - Arancibia-Castro, Kruzkerry (2020)
Objetive: Describe the clinical-epidemiological characteristics and the microbiological profile of the IAAS of the Base Hospital Almanzor Aguinaga Asenjo. Material and methods: observational, descriptive study. Information was obtained from the data sheets of patients included in the point prevalence studies in the 2014 II, 2015 I-IV and 2016 I-II periods, obtained from the Office of Sanitary Intelligence. In addition, the results of the crops were reviewed through the VITEK automated system. A descriptive analysis was carried out by measures of central tendency and percentages. Results: 1617 patients were evaluated, 144 patients were identified with IAAS. The overall prevalence was 9% (9.7%, 10.1%, 8.5%, 6.3% and 10.4% in the 2014, 2015-I, 2015-IV, 2016-I, 2016-II periods). 54.2% were men, the prevalent age group was older adults, the attributable mortality was 12.5%. The most common IAAS was pneumonia (38.9%), followed by urinary tract infections (27.9%), operative site infection (16.2%). Klebsiella pneumoniae, Escherichia coli, sensitive to aminoglycosides and carbapenems, resistant to peniilins, cephalosporins and quinolones were isolated. Pseudomonas aeuruginosa; Resistant to penicillins and carbapenems, sensitive to aminoglycosides Conclusion: The prevalence of intrahospital infections found is in the expected range, with Klebsiella pneumoniae being more prevalent than other studies.